“No, I Will Not Hide from the Great Mess…”: Mandelstam and Akhmatova - Bartoshevich-Zhagel, Olga (Literatūra, 2020)
This paper is devoted to the analysis of Osip Mandelstam’s poem “No, I will not hide from the great mess.” The poem is well-known yet remains relatively obscure and understudied, the meaning of most of its images is not clear. On the basis of motive analysis, draft versions of the poem (as analyzed by I. M. Semenko), and memoirs, a new interpretation is proposed: the addressee and the antagonist of the poem is Anna Akhmatova. The lyrical hero of the poem rides in a tram in the 1930s and painfully recalls the trips on a carriage with Akhmatova in 1917–1918. This interpretation allows to clarify the semantics of all the elements of the poem: its desperate and “rippling” intonation, the motive of the carriage driver, the motive of the game, the image of the “whore,” the comparison with a sparrow, etc. All of these images have a biographical connotation, related to Mandelstam’s relationship with Akhmatova.